(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Gastric ulcer disease is a chronic inflammatory disorder of the gastrointestinal tract that continues to represent a significant medical and social problem worldwide. Despite major advances in diagnostic techniques and pharmacological treatment, the disease is still associated with frequent relapses, complications, and a decline in quality of life. In recent years, increasing attention has been focused on the role of immune and inflammatory mechanisms in the pathogenesis of gastric ulcer disease. Cytokines are key mediators that regulate inflammatory reactions, immune responses, and tissue repair processes in the gastric mucosa. An imbalance between pro-inflammatory and anti-inflammatory cytokines leads to persistent inflammation, increased mucosal damage, and delayed ulcer healing. This study aimed to investigate pathogenetic changes in the cytokine system in patients with gastric ulcer disease and to evaluate their clinical and diagnostic significance. The study was conducted at the Khorezm Multidisciplinary Medical Center and included patients with endoscopically confirmed gastric ulcer disease and a control group of healthy individuals. Serum levels of tumor necrosis factor-alpha, interleukin-1β, interleukin-6, and interleukin-10 were assessed using enzyme-linked immunosorbent assay. The results demonstrated significantly increased levels of pro-inflammatory cytokines and reduced levels of anti-inflammatory cytokines in patients with gastric ulcers. A more pronounced cytokine imbalance was observed in patients with severe clinical manifestations and larger ulcer defects. These findings confirm the important pathogenetic role of cytokine dysregulation in gastric ulcer disease and suggest that cytokine profiling may be useful for assessing disease activity, severity, and treatment effectiveness.